Does season or captivity influence the physiology of an endangered marsupial, the numbat (Myrmecobius fasciatus)? - Cooper, Christine; Withers, P (American Society of Mammalogists, 2012)
We examined the effects of season and captivity on several commonly measured physiological variables (body temperature, metabolic rate, thermal conductance, and evaporative water loss [EWL]) for the numbat (Myrmecobius fasciatus), an endangered myrmecophagous Australian marsupial, because the maintenance of a wild-type physiology may increase the likelihood of successful reintroduction of numbats into the wild. Our results indicate that the physiology of male captive numbats is representative of wild individuals, at least at thermoneutrality, except for some diet-related effects on substrate metabolism and thermoregulation. Season significantly influenced physiological variables, in particular basal metabolic rate (BMR) and EWL. BMR was 30–37% higher in winter than in summer, and EWL increased at a high ambient temperature (Ta) in winter, presumably reflecting seasonal differences in Ta, food availability, and water consumption. Seasonal variation in physiological responses of captive numbats was similar to that observed for wild numbats. We conclude that there is seasonal flexibility in the physiology of numbats, and that captivity under seminatural conditions does not compromise their basic physiology.